Rapid prototyping: applications in oral and maxillofacial surgery - Giovacchini Francesco; Gilli Massimiliano; Mitro Valeria; Monarchi Gabriele; Bensi Caterina; Tullio Antonio (EDP Sciences, 2021)
This article documents four mandibular reconstructions performed using free fibula flaps. CT scan DICOM (Digital Imaging and COmmunication in Medicine) files were obtained in order to print stereolithographic models of the mandible, and in one case cutting guides for fibular osteotomies. One case study details the treatment a cancer recurrence on a right emimandibulectomy. Because of a lack of access to previous CT scans, the left part of the mandible was mirrored to obtain an accurate 3D model. In one case, due to the young age of the woman, a double barrel fibula flap was used. All cases resulted in satisfactory chewing function and aesthetic outcome, with no flap failures. The report concludes that Virtual Planning and Rapid Prototyping are helpful as they reduce costs and intraoperative times while simultaneously improving surgical precision.